PENGUATAN NILAI-NILAI TOLERANSI OLEH MAJLIS TAFSIR AL QUR’AN (MTA) PUSAT SEBAGAI UPAYA MENJAGA KERUKUNAN ANTAR UMAT BERAGAMA DI KOTA SURAKARTA - Diky Setiawan; Rima Vien Permata Hartanto; Mohammad Muchtarom (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2019)
The purpose of this study are 1) to describe the implementation of strengthening tolerance values by Majlis Tafsir Al Qur'an (MTA) Center, 2) to describe the impact of strengthening the tolerance values by Majlis Tafsir Al Qur'an (MTA), 3) to know the supporting factors and the inhibitors of strengthening tolerance value by Majlis Tafsir Al Qur'an (MTA) as an effort to maintain the harmony between one and another religious groups. This study uses a qualitative research approach, this type of research is described qualitatively. The data sources are obtained from informants, places, events, and documents. Based on the results of this study, it can be concluded that (1) The implementation of strengthening tolerance values by Majlis Tafsir Al Qur'an (MTA) Center is carried out through recitation and activities in various fields such as: education, social, and health, which contain values the value of respecting, respecting, accepting differences, and mutual cooperation based on the Qur'an and the Sunnah, (2) The harmony between religious communities in the society is always guarded by Majlis Tafsir Al Qur'an (MTA), this is evidenced in the research findings where there is good relations between the congregation of the MTA and non-Muslim citizens around MTA, (3) The supporting factors of the strengthening of tolerance values in the Majlis Tafsir Al Qur'an (MTA) are: the value of tolerance in the Qur'an and the Sunnah (the Prophet's hadith) in the teachings of Islam, facilitates the strengthening of tolerance values that can be accepted by the congregation, the teaching material is conveyed in a language that is easily understood by worshipers, and the understanding of tolerance in MTA is relatively high. The inhibiting factors are: there is no study material that specifically made to discuss about the values of tolerance, the existence of a society that is easily provoked by issues and slander that develops so that it prevents MTA activities, and there are some individuals (Ex MTA) who vilify MTA. Key words: Strengthening The Tolerance Value, The Harmony Between Religious Communities, Majlis Tafsir Al Qur’an (MTA) Center